Validation of techniques to detect illicit heroin use in patients prescribed pharmaceutical heroin for the management of opioid dependence. - Paterson S; Lintzeris N; Mitchell TB; Cordero R; Nestor L; Strang J (Addiction, 2005)
BACKGROUND: The clinical implementation and evaluation of heroin substitution programmes have been confounded by the lack of objective and validated biomarkers for illicit heroin use in patients prescribed pharmaceutical heroin. This study examined the capacity to detect illicit heroin use by gas chromatography-mass spectrometry (GC-MS) analysis of urine samples for the presence of opium impurities common to illicit, but not pharmaceutical heroin. AIMS: To characterize the diagnostic properties of the metabolites of noscapine and papaverine in comparison to morphine as a gold-standard marker of illicit heroin use; and to examine the relationships between the self-reported time since most recent heroin use and the detection of these opioids in urine. DESIGN: A cross-sectional study of 52 opioid-dependent patients in treatment (not prescribed heroin), who self-reported illicit heroin use within the preceding 2 weeks. Self-report data regarding recent drug use and a urine sample were collected. GC-MS analyses of urines were conducted and reported by laboratory staff blinded to self-report data. FINDINGS: The metabolites of papaverine (hydroxypapaverine and dihydroxypapeverine) were found to have high sensitivity, specificity and negative predictive values as markers for illicit heroin use compared to the 'gold-standard' morphine. Other opioids, including 6-mono-acetylmorphine (6-MAM), codeine and noscapine metabolites (e.g. meconine) were less adequate in detecting heroin use. CONCLUSIONS: GC-MS detection of papaverine metabolites in urine appears to be suitable method of identifying illicit heroin use for clinical and research purposes.